Effect of Assured Transit Time for Perishable Farm Produce on Enhancing Farmers’ Income: A Case Study of Kisan Rail in Context of Mann Ki Baat - Dubey, S K; Singh, Raghwendra; Rau, A A; Kolekar, D V; Athare, Tushar (Indian Journal of Extension Education, 2023)
Transporting the farmers’ produce from field to market in shortest possible time has great potential to curtail farmers’ risk on net profit. Keeping this in view, the Government of India took initiative to operationalize Kisan Rail in August 2020 to fill this gap. The initiative got a fillip through its elaboration in a radio program named Man Ki Baat. The study aimed to answer the research question whether the Mann Ki Baat episode had effect on framers’ knowledge and decision to avail the rail services. Applying a case study approach, the study was carried out in four states of India growing prominent fruit crops including grapes, guava, pomegranate and mango and transporting the produce by Kisan Rail from the site of production to distant places. The respondents selected for the study comprised of 8 groups of 20-25 farmers each. Thus, the total sample size for all the four fruit crops included was 200 respondents. The data were collected using personal interviews and Focus Group Discussions and were analyzed using descriptive statistics. The results showed that an appreciable number of farmers got sensitized, and mobilized to avail the services of Kisan Rail after 77th episode of ‘Mann Ki Baat’ (aired on 30th May, 2021). With increasing probability of getting benefits through access of ‘Kisan Rail’, farmers perceived that the risk percentage of perishable agro-produce got minimized. Grape grower farmers from Nasik (Maharashtra)earned a net profit of Rs. 70.0 Lakh by supplying 22.2 thousand quintal by using Kisan Rail. Whereas, pomegranate farmers of Solapur (Maharashtra) supplied 2.0 thousand quintals of pomegranate and earned a net profit of Rs. 5.40 Lakh. From Raipur, farmers’ group transported 0.54 thousand quintals of guava and earned the net profit of Rs. 0.54 Lakh. The highest net profit of Rs. 28000/ q was secured by mango transportation (2.50 th.q) by a group of farmers from Chikkaballapur (Karnataka). The study suggests that kisan rail facilitated the transport of farmers’ produce from one place to another, secured higher net profit, and minimized the losses, and reduced the involvement of middleman.
Keywords: Mann Ki Baat; Kisan Rail; Fruits; Distant marketing; Farmers’ income